Cor pulmonale in canine patients (Veterinary Science, 2020)
When we talk about cor pulmonale or pulmonary heart disease we refer to a heart that has been disrupted its structure and, therefore, its function as a result of chronic pulmonary disease. Many pulmonary abnormalities can cause this disorder at heart level but all of that arecharacterized by increased vascular resistance or high blood pressure in the lungs. This condition causes right - sided heart failure. So, pulmonary heart disease or cor pulmonale is the enlargement (hypertrophy and sometimes dilation) and failure of the right ventricle as a response to pulmonary hypertension. This paper describes this disease in a mixed breed eleven-year-old canine, which arrived in consultation with decay, anorexy and dyspnea. A complete clinical examination, and then two-dimensional and M-mode echocardiography, doppler echocardiography, chest x-ray and electrocardiography were carried out.
Keywords: pulmonary hypertension; two-dimensional echocardiography; M-mode echocardiography; doppler echocardiography; electrocardiography